2020
DOI: 10.1155/2020/6685740
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Relationship between the Mean Platelet Volume and Carotid Atherosclerosis and Prognosis in Patients with Acute Cerebral Infarction

Abstract: Objective. To investigate the relationship between mean platelet volume (MPV) level and carotid atherosclerosis and prognosis in patients with acute cerebral infarction. Methods. A retrospectively included 160 patients with acute cerebral infarction classified by TOAST classification as aortic atherosclerosis as the observation group. To analyze the relationship between MPV and carotid atherosclerosis, and use receiver operating characteristic (ROC) curves to analyze the role of MPV in predicting the prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Acute cerebral infarction is a local, cerebral, blood supply disorder. Caused by a variety of reasons, it can lead to cerebral ischemia and hypoxia, with the corresponding clinical manifestations of neurological dysfunction (13).…”
Section: Discussionmentioning
confidence: 99%
“…Acute cerebral infarction is a local, cerebral, blood supply disorder. Caused by a variety of reasons, it can lead to cerebral ischemia and hypoxia, with the corresponding clinical manifestations of neurological dysfunction (13).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a correlation between MPV levels and adverse outcomes of AIS (Zhang et al, 2017; Zhang, Zhang, et al, 2017). Recently, researchers found that MPV was closely related to the degree of carotid atherosclerosis, and increased MPV was an independent predictor of poor functional outcome in patients with AIS at 3 months (OR: 6.152, 95% CI: 2.385–13.625, p < 0.01) (Xu, He, & Huang, 2020). As far as we know, there are no studies to observe effects of drug intervention on MPV.…”
Section: Discussionmentioning
confidence: 99%
“…MPV and PC were observed to be independent risk factors for ischemic stroke (Mayda‐Domac et al., 2010 ; Sadeghi et al., 2020 ). Previous studies have suggested that MPV is associated with the prognosis of AIS (Du et al., 2016 ; Greisenegger et al., 2004 ; Wan & Ma, 2017 ; Xu et al., 2020 ; Yang et al., 2019 ; Ye et al., 2020 ), although some studies have reported contradictory findings (Du et al., 2016 ; Mayda‐Domac et al., 2010 ). The studies of PC have mostly been related to cardiology and showed that PC was an independent risk factor for cardiovascular mortality in acute myocardial infarction (AMI) patients (Goliasch et al., 2013 ; Ly et al., 2006 ; Song et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%